Morphometric Analysis of Apis dorsata Bees in North Lombok Regency - Herlambang, Dany Alfian; Hasbihan, M. Nu'aim; Erwan, Erwan; Muhsinin, Muhammad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The giant honeybee (Apis dorsata) is vital for ecosystems as a pollinator, significantly impacting agricultural productivity, biodiversity, and food sustainability. This study explores the morphometric characteristics of Apis dorsata populations in Batu Rakit Village, North Lombok Regency, a tropical region with rich biodiversity. Morphometric data were collected from 20 worker bees, focusing on body length, abdomen dimensions, wing dimensions, proboscis length, and body weight. Measurements were analyzed using descriptive statistics, correlation, and regression to identify significant relationships between morphometric traits and body weight. Results show that abdomen length (r = 0.50, β = 0.05, p = 0.01) and forewing length (r = 0.48, β = 0.08, p = 0.03) are the strongest predictors of body weight, underscoring their roles in resource storage and flight efficiency. Most traits exhibited low variability, reflecting evolutionary adaptations to environmental stability, while body weight displayed high variability (CV = 7.53%), indicating responses to environmental and individual factors. These findings highlight the ecological importance of uniform traits such as abdomen length and wing dimensions in supporting the foraging efficiency and resource transport of Apis dorsata. This study provides critical insights for the conservation and management of Apis dorsata populations in tropical ecosystems.